The Influence of Debt Equity Ratio (DER), Earning Per Share (EPS), Net Profit Margin (NPM) and Return on Equity (ROE) on Stock Returns (Study of the Cigarette Industry that Goes Public on the Indonesian Stock Exchange for the 2011-2021 Period) - Azimah Hanifah (DINASTI RESEARCH, 2023)
The capital market is one alternative used by companies to obtain funds. The presence of the capital market increases the choice of sources of funds for investors and increases investment choices, which can also be interpreted as opportunities to obtain returns. Investment is a commitment to a certain amount of funds or other data sources made at this time with the aim of obtaining a number of profits in the future. This research aims to find the influence of Debt Equity Ratio, Earning Per Share, Net Profit Margin, Return on Equity, Stock Return in the Cigarette Industry that Goes Public on the Indonesian Stock Exchange for the 2011-2021 Period. This research uses an expanatory approach. The object of this research is the cigarette industry listed on the Indonesian stock exchange starting from 2011-2021 on 3 companies which was analyzed using path analysis. From the test results it can be seen that the Debt Equity Ratio (DER), Earning Per Share (EPS), Net Profit Margin (NPM) and Return on Equity (ROE) on Stock Returns is positive and significant. However, if viewed partially, Return on Equity (ROE) has a more dominant influence on Stock Returns. This can be understood because each indicator of Debt Equity Ratio (DER), Earning Per Share (EPS), Net Profit Margin (NPM) and Return on Equity (ROE) is used as an aspect of measuring Stock Returns.